Planning for the overall activities of young biathletes for a year macrocycle - V'yacheslav Mulik (Kharkiv State Academy of Physical Culture, 2015)
Purpose: to determine the number of events and their distribution within a year of the macrocycle in young biathletes. Material and Methods: theoretical analysis and generalization of scientific and methodical literature, analysis of competitive activity of young biathletes, polls and surveys, methods of mathematical statistics. Results: it is determined that the competition for a year macrocycle should have a systemic nature, which would take into account: a gradual increase in the number of starts and long distances; effectiveness of individual competition using specially-preparatory funds at certain stages of training; waviness use the amount of competition for, first of all, the preparatory period and the variability in each individual mesocycle. Conclusions: on the basis of the study the author suggests an optimal distribution of the annual competition for the macrocycle with various competitive disciplines